2017
DOI: 10.1016/j.biombioe.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Valorising faba bean residual biomass: Effect of farming system and planting time on the potential for biofuel production

Abstract: Research was carried out in southern Italy with the aim to assess the quality of faba bean residual biomass and its potential for biorefinery application. Faba bean is a sustainable crop, due to its ability to fix atmospheric nitrogen, and a large amount of biomass remains after harvest which can be valorised for energy production. Greenhouse and early planting are known to affect pod yield and, in this respect, even the residual biomass quality needs to be assessed. For this purpose, the effects of five plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 22 publications
(32 reference statements)
0
18
1
Order By: Relevance
“…Contents of cellulose, hemicellulose, pectin, crystalline cellulose, and non-cellulosic monosaccharide were performed in compliance with a previous study [25], as reported in the following. Holocellulose was determined by delignification of biomass dry powder (7.5 g) for 3 h at 75 °C in a mixture (240 mL water, 0.75 mL glacial acetic acid and 2.25 g sodium chlorite) to which further acid and chlorite amounts, equal to previous, were hourly added.…”
Section: Residual Biomass Determinationsmentioning
confidence: 99%
“…Contents of cellulose, hemicellulose, pectin, crystalline cellulose, and non-cellulosic monosaccharide were performed in compliance with a previous study [25], as reported in the following. Holocellulose was determined by delignification of biomass dry powder (7.5 g) for 3 h at 75 °C in a mixture (240 mL water, 0.75 mL glacial acetic acid and 2.25 g sodium chlorite) to which further acid and chlorite amounts, equal to previous, were hourly added.…”
Section: Residual Biomass Determinationsmentioning
confidence: 99%
“…The positive effect of AMF application on plant nutritional value may become very important in combination with Se and I biofortification. In this respect, no reports in the literature regard the biochemical characteristics of crop wastes, legumes wastes in particular, with the latter being known as a significant source of energy, fiber, protein, antioxidants, and fatty acids [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, Ellis et al (1988) found that optimal flowering progress occurs at 19.9-25.4°C, or even at lower temperature with some genotypes. Due to these requirements, faba bean crop cycle starts in autumn in mild climate areas and in spring in cooler ones, but the optimal planting time for maximizing earliness, yield and quality is strictly matched to the growing environment (Myers et al, 1982;Gomez et al, 2017). In this regard, in Pakistan, Khalil et al (2010) reported that the highest yield is favored by early October sowing, compared to late summer or midautumn planting, and Fasheun and Balogun (1992) detected the significant correlation between dry matter production and radiation use efficiency as affected by planting time.…”
Section: Introductionmentioning
confidence: 99%